Host genetic loci LZTFL1 and CCL2 associated with SARS-CoV-2 infection and severity of COVID-19. (September 2022) - Rüter, Jule; Pallerla, Srinivas Reddy; Meyer, Christian G.; Casadei, Nicolas; Sonnabend, Michael; Peter, Silke; Nurjadi, Dennis; Linh, Le Thi Kieu; Fendel, Rolf; Göpel, Siri; Riess, Olaf; Kremsner, Peter G.; et al.
Highlights: Host genetic factors impact susceptibility to and severity of COVID-19 The 3p31.21 locus replicates as a risk factor for severe COVID-19 The CCL2 polymorphism rs1024611 is associated with susceptibility to infection A polygenic risk score can predict hospitalization in patients with COVID-19 Abstract: Objectives: Host genetic factors contribute to the variable severity of COVID-19. We examined genetic variants from genome-wide association studies and candidate gene association studies in a cohort of patients with COVID-19 and investigated the role of early SARS-CoV-2 strains in COVID-19 severity. Methods: This case-control study included 123 COVID-19 cases (hospitalized or ambulatory) and healthy controls from the state of Baden-Wuerttemberg, Germany. We genotyped 30 single nucleotide polymorphisms, using a custom-designed panel. Cases were also compared with the 1000 genomes project. Polygenic risk scores were constructed. SARS-CoV-2 genomes from 26 patients with COVID-19 were sequenced and compared between ambulatory and hospitalized cases, and phylogeny was reconstructed. Results: Eight variants reached nominal significance and two were significantly associated with at least one of the phenotypes "susceptibility to infection", "hospitalization", or "severity": rs73064425 in LZTFL1 (hospitalization and severity, P <0.001) and rs1024611 near CCL2 (susceptibility, including 1000 genomes project, P  = 0.001). The polygenic risk score could predict hospitalization. Most (23/26, 89%) of the SARS-CoV-2 genomes were classified as B.1 lineage. No associations of SARS-CoV-2 mutations or lineages with severity were observed. Conclusion: These host genetic markers provide insights into pathogenesis and enable risk classification. Variants which reached nominal significance should be included in larger studies.